2020
DOI: 10.3390/rs12223684
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Active Canopy Sensor Mounted on an Unmanned Aerial Vehicle to Monitor the Growth and Nitrogen Status of Winter Wheat

Abstract: Using remote sensing to rapidly acquire large-area crop growth information (e.g., shoot biomass, nitrogen status) is an urgent demand for modern crop production; unmanned aerial vehicle (UAV) acts as an effective monitoring platform. In order to improve the practicability and efficiency of UAV based monitoring technique, four field experiments involving different nitrogen (N) rates (0–360 kg N ha−1) and seven winter wheat (Triticum aestivum L.) varieties were conducted at different eco-sites (Sihong, Rugao, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 76 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…Trilateral parameters, especially red edge parameters, effectively reflect the characteristics of crop N status [ 49 , 50 ]. Studies on wheat, rice, and other crops developed N content estimation models based on red edge parameters, which achieved satisfactory results [ 51 , 52 ]. In this study, we established that the correlation between blue edge parameters and petiole NO 3 − –N contents was strong, and that the traditional regression model of blue edge parameters and petiole NO 3 − –N content was superior to the red edge and yellow edge parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Trilateral parameters, especially red edge parameters, effectively reflect the characteristics of crop N status [ 49 , 50 ]. Studies on wheat, rice, and other crops developed N content estimation models based on red edge parameters, which achieved satisfactory results [ 51 , 52 ]. In this study, we established that the correlation between blue edge parameters and petiole NO 3 − –N contents was strong, and that the traditional regression model of blue edge parameters and petiole NO 3 − –N content was superior to the red edge and yellow edge parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Sihong County (117 • 56 -118 • 46 E, 33 • 08 -33 • 44 N) [25], the study area, is located in the northwestern part of Jiangsu Province, China. The terrain is dominated by plains, with scattered granite and hills distributed in the west and southwest [26]. The location of the study area and its terrain are shown in Figure 1a,b (ground elevation data from http://www.gscloud.cn, accessed on 1 March 2022).…”
Section: Study Areamentioning
confidence: 99%
“…At the winter wheat key stages (DAS210-DAS240) (Du et al, 2017;Yue et al, 2017;Ji et al, 2020;Jiang et al, 2020;Tao et al, 2020a), crop parameters (LAI and SPAD) were measured on DAS210, DAS229, and DAS240. Sixty sets of samples (LAI [30 sets] and SPAD [30 sets]) were obtained every 7 days.…”
Section: Research Measurementsmentioning
confidence: 99%